Corrosion mitigation for steel in acid environment using novel p-phenylenediamine and benzidine coumarin derivatives: synthesis, electrochemical, computational and SRB biological resistivity. Issue 45 (13th October 2022) - Elaryian, Hani M.; Bedair, Mahmoud A.; Bedair, Ahmed H.; Aboushahba, Rabab M.; Fouda, Abd El-Aziz S.
Abstract : Three novel p -phenylenediamine and benzidine coumarin derivatives were synthetized (PhODB ), (BODB ) and (DODB ), these compounds showed excellent anti corrosion effect for steel in 1.0 M HCl and significant SRB resistance. Abstract : Three novel p -phenylenediamine and benzidine coumarin derivatives were synthetized, namely: 4, 4′-((((1, 4-phenylenebis(azaneylylidene))bis(ethan-1-yl-1-ylidene))bis(2-oxo-2 H -chromene-3, 6-diyl))bis(diazene-2, 1-diyl))dibenzenesulfonic acid (PhODB ), 4, 4′-(((-([1, 1′-biphenyl]-4, 4′-diylbis(azaneylylidene))bis(ethan-1-yl-1-ylidene))bis(2-oxo-2 H -chromene-3, 6-diyl))bis(diazene-2, 1-diyl))dibenzenesulfonic acid (BODB ) and 4, 4′-(((-((3, 3′-dimethoxy-[1, 1′-biphenyl]-4, 4′-diyl)bis(azaneylylidene))bis(ethan-1-yl-1-ylidene))bis(2-oxo-2 H -chromene-3, 6-iyl))bis(diazene-2, 1-diyl))dibenzenesulfonic acid (DODB ). Their chemical structures were proved by performing Fourier-transform infrared spectroscopy, proton nuclear magnetic resonance and mass spectrometry analysis. The synthesized p -phenylenediamine and benzidine coumarin derivatives were tested as corrosion inhibitors for mild steel (MS) in 1 M HCl solution using weight loss, electrochemical, morphological, and theoretical studies. The compound 3, 3′-dimethoxy benzidine coumarin derivative (DODB ) was proved to give the highest efficiency with 94.98% obtained from weight loss measurements. These compounds are mixed inhibitors, as seen by the polarization curves. Impedance diagrams showed that when the concentration of these derivatives rose, the double-layer capacitance fell and the charge transfer resistance increased. Calculated thermodynamic parameters were computed and the mechanism of adsorption was also studied for the synthesized p -phenylenediamine and benzidine coumarin derivatives. The ability of the synthesized derivatives to protect the surface against corrosion was investigated by scanning electron microscope (SEM), UV-visible spectroscopy and energy dispersive X-ray spectroscopy (EDX). Theoretical chemical calculations (DFT) and biological resistivity (SRB) were investigated.